Observations of Particle Loss due to Injection‐Associated Electromagnetic Ion Cyclotron Waves. Issue 2 (5th February 2021) - Kim, Hyomin; Schiller, Quintin; Engebretson, Mark J.; Noh, Sungjun; Kuzichev, Ilya; Lanzerotti, Louis J.; Gerrard, Andrew J.; Kim, Khan‐Hyuk; Lessard, Marc R.; Spence, Harlan E.; Lee, Dae‐Young; Matzka, Jürgen; et al.
Abstract: We report on observations of electromagnetic ion cyclotron (EMIC) waves and their interactions with injected ring current particles and high energy radiation belt electrons. The magnetic field experiment aboard the twin Van Allen Probes spacecraft measured EMIC waves near L = 5.5–6. Particle data from the spacecraft show that the waves were associated with particle injections. The wave activity was also observed by a ground‐based magnetometer near the spacecraft geomagnetic footprint over a more extensive temporal range. Phase space density profiles, calculated from directional differential electron flux data from Van Allen Probes, show that there was a significant energy‐dependent relativistic electron dropout over a limited L ‐shell range during and after the EMIC wave activity. In addition, the NOAA spacecraft observed relativistic electron precipitation associated with the EMIC waves near the footprint of the Van Allen Probes spacecraft. The observations suggest EMIC wave‐induced relativistic electron loss in the radiation belt. Plain Language Summary: Electromagnetic waves caused by plasma particles in the Earth's magnetic fields are known to interact with high energy particles in the Earth's radiation belts, leading to loss of the particles into the Earth's atmosphere. We report on observations of the wave phenomena and their interaction with radiation belt particles using data from NASA's twin spacecraft mission called Van Allen Probes. Particle detectors aboard the spacecraft measured the increased flux of particles, providing the source energy to generate electromagnetic waves. Such wave activity was also observed by instruments on the ground. A parameter calculated using data from various instruments aboard the spacecraft enabled us to quantitatively assess how the radiation belt electron population changes over time. This analysis reveals that the wave event caused the radiation belt electrons of certain energies to decay over a limited spatial extent. In addition, particle data from low earth orbiting spacecraft show an increase in particle flux, which appears to be associated with the wave activity. The observations suggest that the wave can contribute to loss of electrons in the radiation belts. Key Points: A radiation belt electron dropout was observed during injection‐associated electromagnetic ion cyclotron (EMIC) waves L ‐shell and energy‐dependent electron dropout indicates EMIC‐wave induced scattering of radiation belt electrons NOAA spacecraft data show relativistic electron precipitation during the dropout event